2007
DOI: 10.1074/jbc.m601317200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Protein Kinase C-mediated Phosphorylation of the Complement C5a Receptor on Serine 334

Abstract: Upon agonist binding, the C5a anaphylatoxin receptor (C5aR) is rapidly phosphorylated on phosphorylation sites that are located within the C-terminal domain of the receptor. Previous studies suggested that C5aR phosphorylation proceeds in a hierarchical manner with serine 334 presenting a highly accessible priming site that controls subsequent phosphorylation at other positions. To better understand the dynamics of Ser-334 phosphorylation, we generated site-specific monoclonal antibodies that specifically reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…CD88 undergoes phosphorylation in response to agonist stimulation resulting in their desensitization (Christophe et al, 2000;Braun et al, 2003). Furthermore, phosphorylation-deficient mutants of CD88 are resistant to desensitization (Pollok-Kopp et al, 2007). Solinski et al (2010) showed that MrgX1 is one of the few GPCRs that does not associate with ␤-arrestin and is resistant to agonist-induced receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
“…CD88 undergoes phosphorylation in response to agonist stimulation resulting in their desensitization (Christophe et al, 2000;Braun et al, 2003). Furthermore, phosphorylation-deficient mutants of CD88 are resistant to desensitization (Pollok-Kopp et al, 2007). Solinski et al (2010) showed that MrgX1 is one of the few GPCRs that does not associate with ␤-arrestin and is resistant to agonist-induced receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, internalization of the receptor, one mechanism for desensitization, was found to be dependent only on amino acids 335-350 in a series of truncated C5a 1 receptor mutants, beyond the majority of the phosphorylation sites . Similarly, another study found that although Ser334, Ser327, Ser332, and Ser338 could be phosphorylated by PK-Cb, these sites were functionally redundant for internalization and desensitization and even that, at high concentrations of C5a, b-arrestin binding to the C terminus could actually inhibit phosphorylation (Pollok-Kopp et al, 2007). Thus, the role of phosphorylation in the control of receptor function remains unclear.…”
Section: A Introductionmentioning
confidence: 99%
“…These sites could be primed for internalization by phosphorylation, as indicated for C5a receptor [36], vasopressin and oxytocin receptors [3, 15] and opioid receptors [18]. Physical association with protein kinases and arrestins could in turn help mobilization of masked receptors.…”
Section: Discussionmentioning
confidence: 99%